Amyloid pathology‐produced unexpected modifications of calcium homeostasis in hippocampal subicular dendrites. Issue 2 (6th January 2020) - Angulo, Sergio L.; Henzi, Thomas; Neymotin, Samuel A.; Suarez, Manuel D.; Lytton, William W.; Schwaller, Beat; Moreno, Herman
Abstract: Introduction: Alzheimer's disease (AD) is linked to neuronal calcium dyshomeostasis, which is associated with network hyperexcitability. Decreased expression of the calcium‐binding protein cal‐ bindin‐D28K (CB) might be a susceptibility factor for AD. The subiculum is affected early in AD, for unknown reasons. Methods: In AD, CB knock‐out and control mice fluorescence Ca 2+ imaging combined with patch clamp were used to characterize Ca 2+ dynamics, resting Ca 2+, and Ca 2+ ‐buffering capacity in subicular neurons. CB expression levels in wild‐type and AD mice were also analyzed. Results: The subiculum and dentate gyrus of wild‐type mice showed age‐related decline in CB expression not observed in AD mice. Resting Ca 2+ and Ca 2+ ‐buffering capacity was increased in aged AD mice subicular dendrites. Modeling suggests that AD calcium changes can be explained by alterations of Ca 2+ extrusion pumps rather than by buffers. Discussion: Overall, abnormal Ca 2+ homeostasis in AD has an age dependency that comprises multiple mechanisms, including compensatory processes.